Transient cortical blindness after coronary angiography. Issue 6 (December 1993) - Parry, R; Rees, J R; Wilde, P
Abstract : Transient visual loss lasting three days developed after transfemoral coronary angiography in a 62 year old man. Computed tomography (CT) showed bilateral leakage of contrast medium into the occipital cortex. A repeat CT scan after his sight recovered showed clearance of contrast with no underlying infarction. A breakdown of the blood-brain barrier with direct neurotoxicity of the contrast media seemed to be the cause of these neurological changes after coronary angiography which apparently have not been reported before.